Perceraian Ditinjau dari Sudut Pandang Etika Kristen dan Implikasinya dalam Dunia Pelayanan - Herman, Samuel; Dharmawan, Rinaldi (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
In the journey of marriage, challenges serve as tests for the commitments uttered in the sacred vow before God. Despite Christianity's rejection of divorce, the reality reveals cases of marital dissolution. This research employs a qualitative literature review approach, delving into Biblical verses to address the ethical concerns surrounding divorce in the context of Christian values. The study explores whether individuals who have experienced divorce can remain active in church service, illustrating diverse perspectives within the Christian community. The research focuses on providing solution-oriented views to facilitate recovery and support for those undergoing divorce while upholding Christian ethical norms. Marriage is not merely a formality but a sacred calling to complement one another, grounded in loyalty and affection. The integrity of marriage is sustained through adherence to Biblical teachings and the example set by Jesus Christ, perceived as a calling to make a positive impact on couples and society.